Topochemical Synthesis of Two-Dimensional Transition-Metal Phosphides Using Phosphorene Templates - Yang, Sheng; Chen, Guangbo; Ricciardulli, Antonio Gaetano; Zhang, Panpan; Zhang, Zhen; Shi, Huanhuan; Ma, Ji; Zhang, Jian; Blom, Paul W. M.; Feng, Xinliang (Angewandte Chemie International Edition, 2020)
Transition-metal phosphides (TMPs) have emerged as a fascinating class of narrow-gap semiconductors and electrocatalysts. However, they are intrinsic nonlayered materials that cannot be delaminated into two-dimensional (2D) sheets. Here, we demonstrate a general bottom-up topochemical strategy to synthesize a series of 2D TMPs (e.g. Co2P, Ni12P5, and CoxFe2−xP) by using phosphorene sheets as the phosphorus precursors and 2D templates. Notably, 2D Co2P is a p-type semiconductor, with a hole mobility of 20.8 cm2 V−1 s−1 at 300 K in field-effect transistors. It also behaves as a promising electrocatalyst for the oxygen evolution reaction (OER), thanks to the charge-transport modulation and improved surface exposure. In particular, iron-doped Co2P (i.e. Co1.5Fe0.5P) delivers a low overpotential of only 278 mV at a current density of 10 mA cm−2 that outperforms the commercial Ir/C benchmark (304 mV).
CRIS-Team Scopus Importer:2023-03-20
Keywords: black phosphorus; electrochemistry; topochemistry; transition-metal phosphides; two-dimensional materials